Profile of science teachers of the Municipal Teaching Network of Barra Mansa (Research, Society and Development, 2019)
This article presents the profile of science teachers of basic education of the municipal teaching network of Barra Mansa (SME- BM). To trace this profile, we developed a qualitative study based on data collected in a continuous education in 2017. The objective of this research was to investigate the difficulties and needs of classroom teachers in order to seek possibilities of continuing formation that corresponded to the reality experienced by teachers in school classrooms. The results of the research contribute to broaden the understanding of the challenges of science teachers of SME-BM and provide subsidies for the development of continuing training courses aimed at the exploitation of teachers and the improvement of science education in the municipality.